Discovery of N-arylsulfonyl-3-acylindole benzoyl hydrazone derivatives as anti-HIV-1 agents - Che, Zhiping (2018)
The discovery and development of novel inhibitors with activity against variants of human immunodeficiency virus type 1 (HIV-1) is pivotal for overcoming treatment failure. As our ongoing work on research of anti-HIV-1 inhibitors, 32 N-arylsulfonyl-3-acylindole benzoyl hydrazone derivatives were prepared by introduction of the hydrazone fragments on the N-arylsulfonyl-3-acylindolyl skeleton and preliminarily screened in vitro as HIV-1 inhibitors for the first time. Among of all the reported analogues, eight compounds exhibited significant anti-HIV-1 activity, especially N-(3-nitro)phenylsulfonyl-3- acetylindole benzoyl hydrazone (18) and N-(3-nitro)phenylsulfonyl-3-acetyl-6-methylindole benzoyl hydrazone (23) displayed the most potent anti-HIV-1 activity with EC50 values of 0.26 and 0.31 μg/mL, and TI values of >769.23 and >645.16, respectively. It is noteworthy that introduction of R3 as the methyl group and R2 as the hydrogen group could result in more potent compounds. This suggested that introduction of R3 as the methyl group could be taken into account for further preparation of these kinds of compounds as anti-HIV-1 agents.